Alcohol influence on blood pressure and stroke incidence - Kosicka, Teresa; Kara-Perz, Hanna (Przewodnik Lekarza/Guide for GPs, 2006)
In this paper probable pathogenetic mechanisms of alcohol influence on blood pressure and usefulness of reduced alcohol consumption were presented. Alcohol influence on central nervous system was recognized the best, but there is still great interest concerning potential mechanisms responsible for alcohol influence on blood pressure. This comprises influence on blood vessels, atherogenesis, coagulation, neuroendocrine system, electrolyte balance and myocardium. In many investigations strong relationship between alcohol drinking and blood pressure was observed. This relationship may be presented as J-curve which reflects hypo- or over the “press threshold” (10-20 g of alcohol in females and 20-30 g in males) hypertensive effect of alcohol. Apart from amount of alcohol also feeding habits are important in hypertension development; higher risk of hypertension results from drinking alcohol without meals. Hypertension is well-known risk factor of stroke. This is why it is important to establish potential relationship between alcohol consumption (and its influence on hypertension) and stroke incidence. It was observed that small amounts of drunken alcohol prevent from ischaemic stroke while protracted consumption of larger amounts is a risk factor of haemorrhagic stroke. In spite of preventive role of small amounts of alcohol in relation to hypertension, one must remember about potential risk of other diseases resulting from alcohol consumption, like hepatic cirrhosis, pancreatitis, neoplasms and trauma.